(untitled) (Veterinary Science, 2022)
Intestinal diverticula are very common in human medicine, being the most common location in the colon (35-75%) and duodenum (15- 42%). In veterinary medicine they are rare. The present report aims to describe the presence of a duodenal diverticulum in a Boxer breed canine, weighing 25 kg, with brown fur, two years old, whose history reflected sporadic vomiting, weight loss and hyporexia. Undergoing exploratory laparotomy due to the presence of a foreign body in the descending duodenum, the patient presented in situ, a deformation compatible with diverticula, with confirmation of it as histopathological result. Given the presence of gastrointestinal signs in canines, young people in general and Boxer breed in particular, it is suggested to consider the intestinal diverticulum as a pathological entity, within the differential diagnoses.